Hubungan Fenomena Deforestasi dengan Penurunan Populasi Rusa Timor (Cervus timorensis) dan Pentingnya Pendidikan Konservasi bagi Masyarakat di Pulau Lombok - Aulia Zulfaeda; M. Harja Efendi; Nining Purwati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
There is an endemic animal in West Nusa Tenggara namely the Timor Deer (Cervus timorensis). However, the population has decreased over time, and the Timor deer species is categorized as an endangered species by the IUCN. The decline of the Timor Deer population in Lombok island is due to lose its natural habitat in the forest. And one of the causes that is deforestation. Deforestation is the conversion of forests into land for use, such as clearing land for agriculture and plantations. Therefore, to maintain the Timor Deer population in Lombok island, it is also important to balance it with providing knowledge about conservation to the community through conservation education. This research aims to analyze the relationship between the deforestation phenomenon and the decline of the Timor Deer population and the importance of conservation education for the community in Lombok island, West Nusa Tenggara. Using a systematic literature review method by collecting data and literature from several journals. The results show that there is a relationship between the deforestation phenomenon and the decline of the Timor Deer population in Lombok and the importance of conservation education to the community to increase public awareness to protect endemic animals.